SPIRITUAL WELL-BEING, EXISTENTIAL NIHILISM & SUB-CLINICAL DEPRESSION IN YOUNG ADULTS (Contemporary Journal of Social Science Review, 2026)
Spirituality plays a vital role in promoting a healthy lifestyle and providing individuals with a sense of meaning and purpose that can have a profound impact on psychological health. Existential nihilism on the other hand is marked by meaninglessness emptiness and despair. A correlational design and a cross-sectional research approach were used in this investigation. Purposive sampling was used to select 324 participants from various universities ages 18 to 26 (170 men and 154 women) who made up the study sample. Data were collected using the Patient Health Questionnaire (Kroenke Spitzer & Williams 1999) the Existential Nihilism Scale (Forsythe & Mongarian 2023) and the Bidirectional Spirituality Scale (Williamson & Ahmad 2018). Existential nihilism and subclinical depression were found to be positively correlated indicating that those who have higher levels of subclinical depression also tend to have more intense existential nihilism. Additionally, the Bidirectional Spirituality Scale showed that higher levels of spirituality were linked to lower levels of existential nihilism and subclinical depression making it a significant predictor of existential nihilism. Through existential nihilism mediation analysis revealed that spiritual well-being indirectly affects subclinical depression. These findings highlight the protective role of spirituality in reducing depressive symptoms and existential distress underscoring its importance for young adult’s mental health.